PENDIDIKAN SEBAGAI KUNCI PEMBERDAYAAN: MENELUSURI HAK-HAK PEREMPUAN DALAM ISLAM - Arsad Dahri; Riki Saputra; Rusydi AM; Mursal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines in depth women's rights in Islam, focusing on three main areas: education, economics, and politics. The background to this study is based on the prevalence of misunderstandings and discriminatory practices against women that are often associated with Islamic teachings, even though such inequality is more likely caused by patriarchal culture and misinterpretation of religion. The purpose of this paper is to explain Islam's fair view of women, analyze their rights based on authoritative sources (the Qur'an and Hadith), and examine the implementation of these rights in contemporary Muslim societies. This research uses library research methods with a thematic analysis approach to religious texts and related scientific literature. The results of the study show that Islam explicitly guarantees women's rights to pursue knowledge, manage property, and participate in social and political life, as evidenced by figures such as Aisha RA, Khadijah RA, and Nusaibah bint Ka'ab.